Skill components of higher education in the era of sustainable development: an analytical study among university students in Qatar - Alshawi, Ali A. Hadi; Ali, Abdel-Samad M.; Raïq, Hicham (Frontiers in Education, 2023)
Introduction The present study investigates the status of education for sustainable development (ESD) as an approach applied to higher education. This study proposes cognitive, behavioral, and socio-emotional learning as the three dimensions of ESD. It examines the extent to which the current curriculum and educational structures applied by Qatar University (QU) contribute to sustainable development (SD) skills in students' attitudes. Methods Data from 319 students were collected. Factor analysis was performed to regroup skill items within the consistent dimensions of 16 core skills. A multivariate logistic regression analysis was performed to examine the relationship between core skills and the five SD skills. Findings Five logistic regression models were investigated. Model 1 found two predictors that only increase the odds of innovative thinking skills. Model 2 detected five predictors that increase the odds of critical thinking skills. Model 3 defined three predictors that increase the odds of resolving problem skills. Model 4 mentioned four predictors that increase the odds of communication/coordination skills. Model 5 showed two predictors that increase the odds of decision-making skills. Research implications This study introduces new core skills that have been reclassified based on students' real-world experiences. Such findings may help target specific skills and bring significant changes in higher education outcomes.